The value of the expression of endometrial receptors for steroid hormones in patients with endometriosis - N. Yu. Pedachenko; T. L. Shemelko; R. A. Tukhtarian (Kazimierz Wielki University, 2020)
Aim: To elucidate the nature of the expression of progesterone receptors (PR) and estrogen receptors (ER) of the endometrium in patients with endometriosis in order to study the effect of endometriosis therapy on endometrial receptors while taking progestogens and agonists of gonadotropin-releasing hormones (a-GnRH). Materials and Methods. A total of 119 women were examined, including 69 patients with small-sized endometrioma with adenomyosis, who were divided into two subgroups during the study: 35 women received Dienogest therapy, other 34 patients received Diferelin. To study the expression of endometrial steroid receptors, the patients underwent endometrial aspiration biopsy from different points of the uterine cavity before the treatment and after 3 months against the background of the therapy for endometriosis. Results Endometriosis therapy affects the expression pattern of endometrial steroid receptors. While taking Dienogest, the sensitivity of the endometrium to estrogens increases, and the number of cells with a positive response to progesterone receptors is partially reduced. When using gonadotropin-releasing hormone agonists (Dipherelin), the sensitivity of the uterine mucosa to ovarian hormones decreases, which is confirmed by the adequate expression of ER and PR. There is a need for more research on estrogen beta receptors, as well as progesterone receptors A and B, and the related ratios.